Wholesale by mail and online ... - Print Project (New York HarperPerennial, 1999)
"Features internet malls and hundreds of company websites."
Vol. for 2000 also called 22nd ed.
Keywords: Commercial catalogs; Advertising, Direct-mail -- United States -- Directories; Wholesale trade -- United States -- Directories; Teleshopping -- United States -- Directories